2020
DOI: 10.3390/biom10030394
|View full text |Cite
|
Sign up to set email alerts
|

Head-to-Head Comparison of the Incremental Predictive Value of The Three Established Risk Markers, Hs-troponin I, C-Reactive Protein, and NT-proBNP, in Coronary Artery Disease

Abstract: Risk stratification among patients with coronary artery disease (CAD) is of considerable interest to potentially guide secondary preventive therapies. Cardiac troponins as well as C-reactive protein (hsCRP) and natriuretic peptides have emerged as biomarkers for risk stratification. The question remains if one of these biomarkers is superior in predicting adverse outcomes. Thus, we perform a head-to-head comparison between high-sensitivity troponin I (hsTnI), hsCRP, and N-terminal pro-brain natriuretic peptide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…Our findings regarding hs-cTnT and NT-proBNP levels are supported by results from the Ludwigshafen Risk and Cardiovascular Health (LURIC) study [25][26][27] and the AtheroGene cohort study [28]. However, the AtheroGene cohort study described CRP as an appropriate biomarker in this context, whereas in our observations, this was only true for the univariate analysis.…”
Section: Discussionsupporting
confidence: 78%
“…Our findings regarding hs-cTnT and NT-proBNP levels are supported by results from the Ludwigshafen Risk and Cardiovascular Health (LURIC) study [25][26][27] and the AtheroGene cohort study [28]. However, the AtheroGene cohort study described CRP as an appropriate biomarker in this context, whereas in our observations, this was only true for the univariate analysis.…”
Section: Discussionsupporting
confidence: 78%
“…Our results were in line with previous studies that once NT- proBNP was taken into account, hs-CRP did not improve predictions in patients with CAD ( 29 , 30 ). Recently, Nikorowitsch et al ( 19 ) performed a head-to-head comparison between NT-proBNP and hs-CRP in patients with CAD and found that NT-proBNP yielded additional prognostic value beyond hs-CRP. Accordingly, our findings might suggest that NT-proBNP levels may outperform hs-CRP in risk estimation.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with CAD, a multi-marker approach to risk stratification has allowed a powerful short-and long-term prediction of heightened risk of MACE (18)(19)(20)(21). Although information available indicates that NT-proBNP and hs-CRP might provide unique prognostic information in patients with previous MI, no study so far has assessed whether combined use of these biomarkers could improve the risk stratification.…”
Section: Introductionmentioning
confidence: 99%
“…NT-proBNP concentrations are also included as a criterion to enter contemporary clinical trials for HF and serve as a proxy metric to demonstrate the effect of interventions on HF morbidity and mortality [ 10 ]. Previous studies have compared cardiac troponins and NT-proBNP “head-to-head” as prognostic markers in patients with coronary heart disease [ 11 ], elderly hospitalized patients [ 12 ], and patients with cardiogenic stroke [ 13 ]. In contrast, less is known about the different properties of cardiac troponin and NT-proBNP in predicting short-term prognosis in unselected patients with acute dyspnea.…”
Section: Introductionmentioning
confidence: 99%